An exploration of the longitudinal relation between parental feeding practices and child anthropometric adiposity measures from the West Midlands Active Lifestyle and Healthy Eating in Schoolchildren (WAVES) Study. Issue 6 (12th December 2018) - Hurley, Kiya L; Pallan, Miranda J; Lancashire, Emma R; Adab, Peymane; ,
ABSTRACT: Background: Some research suggests that parent or carer feeding practices may influence children's weight patterns, but longitudinal evidence is limited and inconsistent. Objective: The aim of this study was to investigate the relation between various parent or carer feeding practices when a child is aged 7–8 y and proxy measurements of child adiposity at age 8–9 y (weight status, waist-to-height ratio, and body fat percentage). Design: The study was a secondary analysis of data from the West Midlands Active Lifestyle and Healthy Eating in Schoolchildren (WAVES) Study comprising a diverse sample of parents and carers and their children from 54 primary schools in the West Midlands, England [ n = 774 parent-child dyads (53% of the WAVES study sample)]. Information on feeding practices was collected with the use of subscales from the Comprehensive Feeding Practices Questionnaire, completed by the child's main parent or carer (self-defined). Child height, weight, bioelectrical impedance, and waist circumference were measured and converted into 3 proxy measurements of adiposity (weight status, waist-to-height ratio, and body fat percentage). Associations between these measurements and parent or carer feeding practices were examined with the use of mixed-effects logistic regression models. Results: Of the questionnaire respondents, 80% were mothers, 16% were fathers, and 4% were other carers. Median standardized subscale scores ranged from 1.7 (emotion regulation: IQR = 1.0) to 4.0 (monitoring and modeling: IQR = 1.5), and significantly different subscale scores were present between child weight statuses for emotion regulation, pressure to eat, and restriction for weight control. Logistic regression modeling showed that when baseline adiposity measures were included as covariates, all associations between parental feeding practices at age 7–8 y and measures of adiposity at age 8–9 y were attenuated. Conclusions: Observed relations between various parental feeding practices and later adiposity are mitigated by inclusion of the baseline adiposity measure. This finding lends support to the theory of reverse causation, whereby the child's size may influence parental choice of specific feeding practices rather than the child's subsequent weight status being a consequence of these feeding practices.